2000
DOI: 10.1006/viro.1999.0120
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Human Immunodeficiency Virus Type 1 Gag Protein Precursor and Envelope Proteins from a Vesicular Stomatitis Virus Recombinant: High-Level Production of Virus-like Particles Containing HIV Envelope

Abstract: Recombinant vesicular stomatitis viruses have been developed as high-level expression vectors which serve as effective vaccine vectors in animals (Roberts et al., 1998, J. Virol. 72, 4704-4711; Roberts et al., 1999, J. Virol. 73, 3723-3732). Here we show that two genes can be expressed simultaneously from a single, live-attenuated VSV recombinant. The genes used encode the Pr55(gag) protein precursor of HIV-1 (1.7-kb gene) and an HIV-1 envelope (Env) protein (2.4 kb gene). Our results show that VSV can accommo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 39 publications
3
61
0
1
Order By: Relevance
“…In fact, a small reduction in weight loss caused by inclusion of EnvG in the rVSV background was observed (Fig. 2), and we have previously noted that HIV Env expression in VSV vectors has a significant effect on reduction of VSV titers in vitro (8).…”
Section: Discussionmentioning
confidence: 58%
“…In fact, a small reduction in weight loss caused by inclusion of EnvG in the rVSV background was observed (Fig. 2), and we have previously noted that HIV Env expression in VSV vectors has a significant effect on reduction of VSV titers in vitro (8).…”
Section: Discussionmentioning
confidence: 58%
“…We used as a control VSV-rwt, which is an analogous wildtype VSV that was also recovered from plasmid DNA (27). These recombinants express high levels of the appropriate HIV-1 proteins (15,21,22).…”
Section: Resultsmentioning
confidence: 99%
“…rVSVs expressing HIV-1 Env and Gag (VSVGag, VSV-Env, and VSV-GagEnv) have been described previously (15,16,21,22), as has the corresponding recovered wild-type VSV (VSV-rwt) control (27). Stocks of VSV and recombinants were grown on BHK-21 cells.…”
Section: Methodsmentioning
confidence: 99%
“…It synthesizes five subgenomic mRNAs encoding five structural proteins (28). VSV recombinants can be recovered from DNA copies, and foreign genes can be expressed at high levels from multiple sites in the genome (11,14,17,31).It has been reported that cells transiently expressing HCV E1 or E2 chimeric proteins containing the VSV G transmembrane and cytoplasmic domains generate VSV pseudotypes when infected with a VSV mutant (ts045) that is temperature sensitive for G protein transport to the cell surface (16). Pseudotypes formed with either the E1G or E2G constructs were reported to infect mammalian cell lines, including cell lines not derived from the liver.…”
mentioning
confidence: 99%